Attenuated fusogenicity and pathogenicity of SARS-CoV-2 Omicron variant - Suzuki, Rigel; Yamasoba, Daichi; Kimura, Izumi; Wang, Lei; Kishimoto, Mai; Ito, Jumpei; Morioka, Yuhei; Nao, Naganori; Nasser, Hesham; Uriu, Keiya; Kosugi, Yusuke; Tsuda, Masumi; et al. (Nature (London), 2022)
The emergence of the Omicron variant of SARS-CoV-2 is an urgent global health concern 1 . In this study, our statistical modelling suggests that Omicron has spread more rapidly than the Delta variant in several countries including South Africa. Cell culture experiments showed Omicron to be less fusogenic than Delta and than an ancestral strain of SARS-CoV-2. Although the spike (S) protein of Delta is efficiently cleaved into two subunits, which facilitates cell–cell fusion 2 , 3 , the Omicron S protein was less efficiently cleaved compared to the S proteins of Delta and ancestral SARS-CoV-2. Furthermore, in a hamster model, Omicron showed decreased lung infectivity and was less pathogenic compared to Delta and ancestral SARS-CoV-2. Our multiscale investigations reveal the virological characteristics of Omicron, including rapid growth in the human population, lower fusogenicity and attenuated pathogenicity. In vitro studies in human cell lines and in vivo studies in a hamster model show that the SARS-CoV-2 Omicron variant is less pathogenic than both the Delta variant and an ancestral strain of SARS-CoV-2.